RANCANG BANGUN WEBSITE PADA TOKO SEPATU WIASSHOP BERBASIS CUSTOMER RELATIONSHIP MANAGEMENT - Dwi Astuti Wahyuningtyas; Yohanes Suhari (Elkom: Jurnal Elektronika dan Komputer, 2022)
The current era is the era of globalization, and many companies are starting to develop with increasingly sophisticated technology. CRM is a comprehensive tactic from the company so that every process of the customer life cycle can be utilized optimally. The purpose of this study was to establish a website for the CRM-based WiassShop Shoe Store. The method that will be built in this research is a website-based information system at WiasShop using the Waterfall system development method. The use of this method begins with listening to all obstacles, obstacles and suggestions from customers. Then a system design will be carried out that is tailored to the needs and complaints that have been submitted by customers, after which the development design is implemented in the form of a website. After that, the system will be tested to find out where the bugs (weaknesses) are, which will later be repaired and refined. This system will be built using Php Native and using MySQL database. Hasil penelitian yang penulis buat dengan judul Rancang bangun website pada toko sepatu wiasshop berbasis CRM adalah untuk memudahkan pengelola Wiasshop dalam melakukan pengolahan data produk, memudahkan dalam pencatatan data transaksi,dan mempermudah user dalam melakukan pembelian produk.